KECERDASAN SPIRITUAL SEBAGAI PREDIKTOR KESEJAHTERAAN SUBJEKTIF PADA MAHASISWA - Benny Herlena; Nur Ayu Seftiani (UIN Sunan Kalijaga, 2018)
In their first year study of adolescent students commonly met stressor and pressure of adaptation in their novel situation. It can make them have a problem. Adolescents student who can not cope with the problem will be more vulnurable to depression and negative emotions. It can lead them to be unhappy and dissatidfied with their life, but some factors predicted to influence their situation. The purpose of this research was to determine spiritual intelegence can be a predictor ofsubjective wellbeing ofadolescent students. Subject of this research were 116 (N=116) adolescents students (17-18 years old) at UIN Sunan Kalijaga Yogyakarta. Subjective wellbeing scale from Utami (2008) and spiritual intelegence scale from Khalqi (2017) was used to collect data with incidental sampling technique. Datawas analyzed by regression technique analysis. The result of the analysis indicate that spiritual intelegence can be a predictor of students subjective wellbeing withr correlation 0.9033 and p = 0,003 (p < 0,005). It means the hyphotheses stated that spiritual intelegence can be a predictor of students subjective wellbeing was accepted. Furthermore there are 7,03% (R square=0,073) effective contribution of spiritual intelegence toward subjective wellbeing of student.